AN OVERVIEW ON AIR POLLUTION IN INDIA AT PRESENT SCENARIO - chauhan, Pooja (International Journal of Research -GRANTHAALAYAH, 2015)
Environmental conservation became a major concern. Pollution is the major threat in most of regions in the world. India is also witnessing the environmental pollution due to rapid economic growth and insufficient implementation of environmental pollution control measures. Though the measurement of air quality is complicated, there are a few pollutants which regulators keep under supervision through regular monitoring. The most observed pollutants includes PM, NO2, SO2, CO2 etc. This paper aims to provide an overview of environmental pollution especially air pollution and concentration pollutants (PMs, SO2, NO2 etc.).